Efficiency of forward as an instrument for exchange risk coverage in companies performing foreign trade operations, 2011-2017 (2019)
This paper evaluates the efficiency of forward contracts derived from the exchange rate of American dollars / Colombian pesos (USD / COP), as a hedging instrument for foreign exchange risk, to which companies that carry out foreign exchange operations are exposed. For this, the USD / COP spot and forward prices between 2011 and 2017, available in the Colombian Stock Exchange, were analyzed, valuing their risk through the VaR (value at risk) and their impacts as a hedging instrument of risk of exchange rate. In addition to the empirical validation of the forward as a hedging instrument, some inefficiencies of this financial instrument were found, due to its low availability and the high transaction costs in the use of this derivative as a hedging instrument.